Understanding Student- Centered Learning and Philosophies of Teaching Practices - Singhal, Dr. Divya (International Journal of Scientific Research and Management (IJSRM), 2017)
In the context of today‘s volatile, uncertain and complex business environment, the business schools have started to identify the need to be innovative and to produce responsible future leaders. Teaching within higher education has undergone a pedagogical shift in recent years, with new approaches to increase student engagements and thereby learnings. Over the years many theories have been developed to examine the processes involved in effective learning. Most learning theories concentrate on the significance for the way that learning is delivered. There are variety of ways for ensuring learning. The current paper is designed to give the readers an idea about the various philosophical approaches in teaching-learning and describe the ―student Centered‖ pedagogy.